One-shot determination of residual dipolar couplings: application to the structural discrimination of small molecules containing multiple stereocenters - Castañar, Laura (2016)
A novel approach for the fast and efficient structural discrimination of molecules containing multiple stereochemical centers is described. A robust J-resolved HSQC experiment affording highly resolved 1JCH/1TCH splittings along the indirect dimension and homodecoupled 1H signals in the detected dimension is proposed. The experiment enables in situ distinction of both isotropic and anisotropic components of molecules dissolved in compressed PMMA gels, allowing a rapid and direct one-shot determination of accurate residual dipolar coupling constants from a single NMR spectrum.